2001
DOI: 10.1097/00001756-200112210-00061
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in interhemispheric transmission time in the human brain

Abstract: Many studies on hemispheric specialization for language functions and on morphology of the corpus callosum have revealed stronger lateralization and smaller splenium area in men than in women. We have tested the related prediction that interhemispheric transmission times (IHTTs) of verbal information differ in the two sexes using event-related potentials (ERPs) for determining IHTTs in male and female subjects. The IHTTs were estimated as latency differences between early components of ERPs, recorded in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
24
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 28 publications
4
24
0
Order By: Relevance
“…Previous EEG studies that looked at individual differences in IHTT found a shorter overall IHTT in women compared to men (Moes et al, 2007;Nowicka & Fersten, 2001). In addition, IHTTs for left-to-right and right-to-left directions were relatively symmetrical in women, whereas men revealed a directional asymmetry in IHTT.…”
Section: Relationship Between Sex Hormones and Ihttmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous EEG studies that looked at individual differences in IHTT found a shorter overall IHTT in women compared to men (Moes et al, 2007;Nowicka & Fersten, 2001). In addition, IHTTs for left-to-right and right-to-left directions were relatively symmetrical in women, whereas men revealed a directional asymmetry in IHTT.…”
Section: Relationship Between Sex Hormones and Ihttmentioning
confidence: 96%
“…Previous work employing visual-evoked potentials to measure IHTT, revealed a directional asymmetry in conduction velocities between hemispheres (e.g. Barnett, Corballis, & Kirk, 2005;Brown, Larson, & Jeeves, 1994;Iwabuchi & Kirk, 2009;Moes, Brown, & Minnema, 2007;Nowicka & Fersten, 2001;Patston, Kirk, Rolfe, Corballis, & Tippett, 2007;Rolfe, Kirk, & Waldie, 2007;Saron & Davidson, 1989; see also Marzi, 2010, andTacikowski, 2011, for reviews). The transfer of neural information from the right hemisphere to the left is faster than transfer from the left hemisphere to the right.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigation suggests that many perceptive incongruities are rooted in the brain's structural and functional organization. Notably, females have been credited with relatively more left-lateralized language and emotion processing, whereas males often tend toward right-lateralized visuospatial activity (2)(3)(4)(5). Further, sex differences in interhemispheric communication and brain structure volumes suggest variation in how information is processed (2)(3)(4).…”
mentioning
confidence: 99%
“…Notably, females have been credited with relatively more left-lateralized language and emotion processing, whereas males often tend toward right-lateralized visuospatial activity (2)(3)(4)(5). Further, sex differences in interhemispheric communication and brain structure volumes suggest variation in how information is processed (2)(3)(4). If males and females diverge at levels of basic neural processing and structure, questions arise about how more complex levels of information integration are affected and how these differences relate to risk for cognitive and emotional dysfunction.…”
mentioning
confidence: 99%
“…Poffenberger investigated the interhemispheric transfer time (IHTT), stating that it refers to the time taken for transfer of information from one hemisphere to the other hemisphere via the CC, hence reflecting the speed of human information transfer (Poffenberger 1912). Our previous EEG work ( Iwabuchi and Kirk 2009;Rolfe et al 2007), and that of others (Brown et al 1994;Jeeves and Moes 1996;Nowicka and Fersten 2001;Saron and Davidson 1989), have shown that IHTT from the right to the left hemisphere is shorter than that from left to right. It has been proposed, for example, that this is due to the right hemisphere having a greater number of fast-conducting corticocortical connections than the left hemisphere (Miller 1996).…”
Section: Introductionmentioning
confidence: 99%